ANALISIS PEMANFAATAN MEDIA CANVA DALAM MENINGKATKAN MINAT BELAJAR MATA PELAJARAN BAHASA INGGRIS PADA SISWA KELAS 3 DI SD NEGERI KETILENG 2 KOTA CILEGON - Hairul Umam; Desty Endrawati Subroto; Kurniati Rahmadani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the utilization of Canva media in increasing students' interest in learning English for 3rd-grade students at SD Negeri Ketileng 2 Cilegon. Using a qualitative descriptive approach with observation, interviews, and documentation, the results show a significant increase in student engagement after implementing Canva. Students became more active, creative, and motivated in creating posters and visual materials for the "The Zoo" chapter. Canva effectively supports interactive and technology-based learning in elementary schools.